The geology of the country around Nettoseter, Höydalen, Norway - Cowan, D.R. (1966)
The area is part of the north-west Jotunheim mountains in southern Norway and consists of three rn.ain rock units; Granitic rocks of the Basal Gneiss Corn.plex outcrop in the north of the area; supracrustal rocks of presumed Eo-Cambrian to Ordovician age in the central part and the Upper Jotun Nappe outcrops in the south. Previous work in the area (mainly by Nottingham workers) had shown that the supracrustal rocks were thrust onto basal gneisses. The detailed structure of the supracrustal rocks, the relationship of the Upper Jotun Nappe to underlying rocks and structure and the metamorphic history were unknown and little detailed petrography and chemistry of the supracrustal rocks had been carried out. The writer, by means of detailed structural analysis, with petrographic, chemical and mineralogical studies, has attempted to reconstruct the detailed metamorphic and structural history of the supracrustal rocks. The stratigraphy and a description of the lithologies with field relations, petrography and chemistry are given and a special study made of amphibolites and dunite-serpentinites. The structure of the area is complex; Pre-Cambrian structures from the Basal Gneiss Complex and Upper Jotun Nappe and five phases of Caledonian deformation (excluding joints) are recognised. Orientation and symmetry of folds are discussed. Occurrences of conglomeratic structures are described; these are B-tectonites, essentially tectonic inclusions formed by disruption of continuous layers. A quantitative study of fold styles is presented and folding is discussed in kinematic terms; the second Caledonian deformation (BZ) is complex. A movement picture is suggested for each main phase of deformation. A quantitative fold description is considered and BZ folding is discussed from theoretical and experimental points of view. The metamorphic history of the area is described; three Caledonian metamorphisms and several Pre-Cambrian phases described. A tentative geological history is presented and some of the broader aspects of the work discussed. Mineral analyses are presented and a brief description of the methods used given.